PERBEDAAN TINGKAT KECEMASAN PASIEN HEMODIALISA BERDASARKAN SOSIODEMOGRAFI: DIFFERENCES IN ANXIETY LEVELS AMONG HEMODIALYSIS PATIENTS BASED ON SOCIODEMOGRAPHIC FACTORS - Mori Agustina Br Perangin-angin (Journal of Nursing Care and Biomolecular, 2025)
Introduction: Anxiety, stress, and depression are among the most common psychological issues experienced by patients with chronic kidney disease (CKD), due to the high mortality rate associated with the illness both globally and in Indonesia. This study aims to identify anxiety levels among CKD patients undergoing hemodialysis and examine differences based on sociodemographic characteristics. Method: This research employed a descriptive-correlational design with a cross-sectional approach. The population consisted of CKD patients undergoing hemodialysis at a private hospital in Bandung. A total of 88 patients were selected using total sampling. Data were collected using the State-Trait Anxiety Inventory (STAI), comprising 40 items that measure both state and trait anxiety levels. Result: Findings showed that 55.7% of patients experienced severe anxiety. Female patients had a higher mean anxiety score (49.55) than males (40.48). Those undergoing dialysis three times per week showed greater anxiety (46.33) compared to those on a twice-weekly schedule (42.90). Based on employment status, the highest anxiety was observed in retired individuals (51.85), followed by unemployed (46.51), employees (43.12), and self-employed individuals (39.69). However, these differences were not statistically significant (p > 0.05). Discussion: More than half of the patients undergoing hemodialysis experienced high levels of anxiety. Although not statistically significant, anxiety levels were found to be higher among women, patients with more frequent dialysis sessions, and those who were retired. These findings suggest the importance of addressing psychosocial factors in the management of patients undergoing long-term dialysis therapy. Keyword: anxiety, sociodemographic, chronic kidney disease